Fusarium oxysporum and Aspergillus sp. as Keratinase Producers Using Swine Hair From Agroindustrial Residues - Preczeski, Karina Paula; Dalastra, Caroline; Czapela, Fabiane Fernanda; Kubeneck, Simone; Scapini, Thamarys; Camargo, Aline Frumi; Zanivan, Jessica; Bonatto, Charline; Stefanski, Fábio Spitza; Venturin, Bruno; Fongaro, Gislaine; Treichel, Helen (Frontiers in Bioengineering and Biotechnology, 2020)
Technological processes mediated by microorganisms and enzymes are promising alternatives for treatment of recalcitrant residues. Keratinases hydrolyze keratin, the primary component of some wastes generated in many industrial activities. The present study was designed to evaluate strategies for obtaining keratinases produced by fungi using submerged fermentation and two residues as substrates, chicken feathers and swine hair. Two fungi isolated from feather residues showed potential for keratinase production, Fusarium oxysporum and Aspergillus sp. These were subjected to submerged fermentation using chicken feathers and swine hair prepared in three conditions (microbial concentration reduction, sterilization and hydrogen peroxide). The residual mass was quantified and tested for keratinase production. The most potent enzymatic extract was used in the precipitation technique with salts and organic solvents. The best results of enzymatic activity were obtained using F. oxysporum, on the sixth day of fermentation, obtaining 243.25 U mL-1 using sterilized swine hair as the substrate. Aspergillus sp. showed the highest keratinolytic activity on the ninth day, 113.50 U mL-1 using feathers as the substrate. The highest degradation percentage was 59.20% (w/w) in swine hair and the precipitation technique, with relative activities close to 50%. The results are promising for the application of residues and microorganisms in biotechnological processes of economic and environmental interest.